The Effect Of Health Expenditure On Life Expectancy In Bengkulu - Riki Irawan; Pasaribu, Esti (Jurnal Ekonomi, 2024)
This study aims to analyse the effect of health expenditure, access to health services, and poverty on life expectancy in Bengkulu Province from 2014-2023. Using the multiple linear regression method, the results show that health expenditure does not significantly influence life expectancy, which is caused by the budget allocation that is still low and less than optimal. In contrast, access to health services substantially increases life expectancy, whereas people with better access to health services have a higher life expectancy. Poverty was also found to have no significant effect, which may be due to government policies that help people experiencing poverty obtain health services. This study concludes that optimising access to health services is more important than increasing health spending to increase life expectancy.